Intra-Seasonal and Intra-Annual Variation of the Latent Heat Flux Transfer Coefficient for a Freshwater Lake - Gabriella Lükő; Péter Torma; Tamás Weidinger (Atmosphere, 2022)
In the case of lakes, evaporation is one of the most significant losses of water and energy. Based on high-frequency eddy-covariance (EC) measurements between May and September of 2019, the offshore heat and water vapor exchanges are evaluated for the large (~600 km2) but shallow (~3.2 m deep) Lake Balaton (Transdanubian region, Hungary). The role of local driving forces of evaporation in different time scales (from 20 min to one month) is explored, such as water surface and air temperatures, humidity, atmospheric stability, net radiation, and energy budget components. EC-derived water vapor roughness lengths and transfer coefficients (Cq) show an apparent intra-seasonal variation. Different energy balance-based evaporation estimation methods (such as the Priestley-Taylor and the Penman-Monteith) confirm this observation. Furthermore, this has suggested the existence of an intra-annual variation in these parameters. This hypothesis is verified using ten years of water balance measurements, from which, as a first step, evaporation rates and, second, transfer coefficients are derived on a monthly scale. Cq is highly reduced in winter months (~1 × 10−3) compared to summer months (~2.5 × 10−3) and strongly correlated with net radiation. The application of time-varying Cq significantly increases the accuracy of evaporation estimation when the Monin-Obukhov similarity theory-based aerodynamic method is applied. The determination coefficient increases to 0.84 compared to 0.52 when a constant Cq is employed.